2011
DOI: 10.4102/jsava.v82i4.78
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological survey of Rhodococcus equi infection in asymptomatic horses and donkeys from southeast Turkey

Abstract: n order to assess the level of Rhodococcus equi infection in southeast Turkey, 679 sera from healthy foals and adult horses and 78 sera from donkeys were tested by indirect ELISA using a R. equi reference strain (ATCC 33701) as antigen. Eighty (11.7 %) sera from horses and 9 (11.5 %) sera from donkeys with titres >0.85 were positive. The prevalence of seropositive horses in Sanliurfa Province was higher than in Diyarbakir Province; 56 (13.9 %) horses in Sanliurfa Province and 24 (8.7 %) horses in Diyarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…Solmaz et al 10 reported a seroprevalance of 60.59% (123/203) in horses raised in Van province of East Turkey by RBPT and out of these 123 positive serum samples 98 (79.67%) showed 1/40 or higher titers by SAT. The result of another study on horse brucellosis in Southeast Turkey was 13.68 and 0.51% by RBPT and SAT, respectively 11 . If we take a look at the situation in neighbouring countries; in a study conducted in North-East of Iran, the seroprevalence of brucellosis was determined as 2.5% in horses by RBPT and SAT 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Solmaz et al 10 reported a seroprevalance of 60.59% (123/203) in horses raised in Van province of East Turkey by RBPT and out of these 123 positive serum samples 98 (79.67%) showed 1/40 or higher titers by SAT. The result of another study on horse brucellosis in Southeast Turkey was 13.68 and 0.51% by RBPT and SAT, respectively 11 . If we take a look at the situation in neighbouring countries; in a study conducted in North-East of Iran, the seroprevalence of brucellosis was determined as 2.5% in horses by RBPT and SAT 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off value for positive samples was set as the mean OD of the negative control plus 3 standard deviations (s.d. ), which corresponded with 20% seropositivity (Tel et al 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were collected from apparently healthy horses at selected farms that represent the geographic distribution of the equine population in Israel. Because R. equi prevalence in Israel has never been evaluated, sample size was calculated using the estimation that the Israeli equine population consists of approximately 30 000–40 000 horses, and the prevalence that was found in a similar survey from Turkey was about 10% seropositivity in subclinically infected horses (Tel et al 2011 ). With these data, the required sample size for prevalence of 10% ± 5% was 219 horses (Win Pepi 11.43).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations